Performance characteristics of in-situ particle monitors at sub-atmospheric pressures - Bae, Gwi-Nam; Liu, Benjamin Y.H. (Institute of Environmental Sciences - Proceedings, Annual Technical Meeting, 1998)
Since in-situ particle monitors (ISPMs) have been evaluated in the past primarily at atmospheric pressures, their performance characteristics under vacuum conditions are not well understood. The performance of a Particle Measuring Systems (PMS) Vaculaz-2 ISPM at subatmospheric pressures has been studied experimentally in this research. We created uniform upstream conditions of particle concentration and measured the detection efficiency, the lower detection limit, and the particle size response of the ISPM using uniform sized methylene blue aerosol particles. The effect of particle size, particle velocity, particle concentration, and system pressure on the detection efficiency of the detector has been examined.